THE MAIN FACTOR OF THE DEVELOPMENT OF THE NEW ECONOMY POST-INDUSTRIAL SOCIETY - Rakhmanbaeva R.A (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article examines the place and role of human capital in the development of an innovative economy; it is shown that the size and quality of domestic human capital today does not correspond to the country’s declared transition to an innovative society. The author proposes measures to improve human capital and enhance its influence on the formation of an innovative economy.